Redesign of Core Groyne Using Natural Materials - Maulida Amalia Rizki (NAROTAMA UNIVERSITY, Indonesia)
Coastal abrasion is one of the serious problems with shoreline change. In addition to natural processes, such as wind, currents and waves. One method for overcoming coastal abrasion is the use of coastal protective structures, where the structure functions as a wave energy damper at a particular location. Coastal buildings are used to protect the beach against damage due to wave and current attacks. Groyne is a coastal safety structure that is built protrudes relatively perpendicular to the direction of the coast, the importance of built coastal security with a groyne structure on the Jetis beach is as a flood control infrastructure that is as a final disposal of floods in the Ijo Watershed system, addressing coastal abrasion in detail. So we get the design drawings of sediment control buildings to reduce sedimentation / siltation from the direction of the sea into the river mouth, material structure costs and time schedule.